Beach Museum Web Application - Kakkireni, Nithin Kumar (Kansas State University, 2018)
This project involves in developing a responsive web application for Beach Museum at Manhattan, Kansas. Application is built on development boxes using Amazon web services. Project is built on MVC architecture that helps user to search images, create their own collection from the images and include an admin module. Migrating the current existing SQL database to couchDB for better performance of the available data. Integrated Apache Lucene to support text search in the couch database writing different indexes to retrieve the results. Implementing core functionalities like basic search, advanced search, filter objects with respective to artist, decade, object type and relevance using different indexes and Mango queries in the couchDB. Search Results are further chunked and displayed to the user. Web storage API’s were used to provide the functionality for a user to create their own collection (set of Images). Built an Admin module to perform CRUD operations the database. Admin module involves in creating exhibitions, adding/editing works and artists in the couch DB.
Keywords: Web Application; CouchDB; Lucene; Web Storage; Beach Museum